(untitled) (Revista Argentina de Musicología, 2018)
During the period of the Nazi regime, over a hundred Jewish musicians, most of them with musical training and an outstanding professional past in Europe, came into an Argentinian exile. Although their arrival is of great importance for the cultural history of Argentina, local musicology has not studied this particular immigration. The few existing biographies do not dwell on these aspects of their lives: they were Jews and exiles, two traits that not only made them itinerant, but also marked a different course in their path. This article is part of a larger project; here we present the group of musicians we are studying and analyze some specific situations in relation to their arrival in Argentina and the different modes of attachment and employment in various areas of Argentina’s music field in the 1930s and ‘40s.